(untitled) (Research, Society and Development, 2020)
This article originated from the discussions held in the classes of the discipline of Grammar, Variation and Teaching of PROFLETRAS / UEPB and is justified by the need to expand these discussions in the academic and school environment. Thus, the objective was to analyze the use of standard, cultured and colloquial norms in Opinion Articles in the Nova Escola magazine, in line with communicative intentions from different contexts, making a linguistic analysis in relation to the use of these norms, verifying the lexical choices that justify one or the other use of these norms in the construction of these texts according to the communicative intention of the producers, in order to bring the distinction as well as the discursive intentionality between one and another variety. For this purpose, we used as contributions the contributions of Gagné (2002), Antunes (2003), Bakhtin (2003), Veiga (1998), Bagno (2002), Bazerman (2005), among others, which guide the use of the standards mentioned . A descriptive and interpretive bibliographic analysis was used as methodology, presenting the journal’s approach in relation to the use of these variants based on the analysis of three articles that served as the object of study. The results pointed out that the articles produced in the magazine, even though they turned, in general, to teachers, seek to adapt their discursive purpose, to debate issues related to teaching that may include different professionals and not only those of the Portuguese language. Therefore, it is concluded that even with the frequent use of the standard norm, there is a predominance of the cultured and colloquial language ensuring a close relationship between text / reader.